The devil’s allegory as an ironic criticism of capitalism in the work of Machado de Assis - Enoque, Alessandro Gomes (2023)
Among the various analytical paths related to the work of Machado de Assis, one that seems to draw the most attention is the one that seeks approximations between literary and religious discourses (Cantarela, 2015; Alves; Oliveira; Ivan, 2014; Maia, 2015; Silva, 2016; Proença, 2010; Nova, 1992; Schmidt; Silva, 1978; Brum, 2009). In this sense, for Cantarela (2015), there are at least three models of reading the dialogue between religion and literature, namely: (a) the dialogic model of comparative literature (characterized by the search for traces of intertextuality between the Bible and other canonized works by religious traditions with literature); (b) the theorized dialogic model (characterized by the search for theoretical justifications for the dialogue between religion and literature); and, finally, the (c) thematic dialogic model (understands that the interlocution between the theological and literary discourse can be constructed from elements of the lived world and focusing on various themes). For the specific purposes of this article, we opted for an analytical model that includes both the comparative literature dialogic and the thematic dialogic. We followed this path since our objective consists, fundamentally, in analyzing, in Machado’s short stories A Igreja do Diabo and Sermão do Diabo, the way in which the author makes an ironic social critique of Brazilian capitalism at the end of the nineteenth and early twentieth centuries. It is important to highlight that, although some works have the theme of social criticism as a central element (Couto, 2016; Bosi, 2004), none are based on the allegory of the devil.